The 21st Century Dictionary AN-NAFEES English - Arabic = (3eYLe GdbQf GdMGOj hGdYTQjf (B: (3GdfajS EfLdjRj (B- (3YQHjs - Wahba, Magdi (Byrut Librairie du Liban Publishers Cairo Egyptian International Publishing Company - Longman, 2000)
A comprehensive English-Arabic Dictionary; this is the 21st Century Dictionary English-Arabic with the Pronunciation of the English Entries Using a Phonetic Alphabet. Including Appendices, a Colored Section Containing Selections from the Holy Quran, and the Most Beautiful Names of Allah and prophets sayings at the end with color design. This dictionary contains extra pages for the following subject: 16 Pages Selection from the Haddith 16 Pages Selection from the Holy Quran 10 Pages the Most Beautiful Names of Allah
(3Eqfg eYLe GdYUQ hMUGO MjGI LGeYjI heLeYjI ZfjI hYejbI, hNdGUI LghO eYLejI YOjOI, JhL Hg eDdag GYeGdg(B. (3jLeY ajg Hjf GdcdGSjcjI hGdYUQjI, ShGA aj eOGNdg GdEfLdjRjI Ch aj ebGHdGJg GdYQHjI GdJj GNJGQ dgG GdaUjM GdhGVM hGdHSjW ef GdeaQOGJ(B. (3jgJe HGdeUWdMGJ GdYdejI hGdafjI hGdJbfjI, bOjegG MOjKgG, hjYfi HeG CbqQg eLeY GddZI GdYQHjI(B. (3jhdj GdLed hGdYHGQGJ GdGUWdGMjI hGdJQGcjH GddZhjI GdGfcdjRjI GgJeGeG edMhXG, hjhQO eG jbGHdgG aj GdYQHjI ef Led hYHGQGJ GUWdGMjI hJQGcjH dZhjI, HYjOG Yf GdJQLeI GdMQajI(B. (3LejY GdeaQOGJ GdYQHjI eVHhWI HGdTcd GdcGed, hGdeOGNd GdGfcdjRjI eUMhHI HWQjbI daXgG (B((3fWbgG(B)(3, hUjZ GdLeY ZjQ GdeCdhaI, hJUQjaGJ GdGaYGd ZjQ GdbjGSjIs
With the pronunciation of the English entries using a phonetic alphabet
(3eRhO HfWb GdCdaGX GdEfLdjRjIs
(3jTJed Ydi edGMb hdhMGJ edhfI deNJGQGJ ef GdbQBf GdcQje hCSeGA Gddg GdMSfi hGdMOjK GdfHhj GdTQjas
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjIs
2
Keywords: Dictionaries; Dictionaries